Efficient atrazine degradation through ZnFe2O4-catalyzed peroxymonosulphate activation - Junyi Gao; Xuying Zhao; Caibin Li; Zhenbao Luo; Long Zhang; Zhipeng Xiao; Tingting Mu; Furong Liu; Ruikang Gao; Jiguang Zhang; Xiwen Sun (Scientific Reports)
Abstract Atrazine (ATZ) is widely used as an herbicide in agricultural production. However, its extensive application results in contaminated residues that can adversely affect ecosystems because rainwater washes them into and contaminates water bodies. Therefore, there is a pressing need to remove ATZ from the aquatic environment. Using transition metals as catalysts for the persulfate degradation of organic pollutants has received much attention because of their strong ability to oxidize pollutants, including ATZs, and their selectivity for these pollutants. A novel technique for ATZ removal using a catalyst (ZnFe2O4) to activate peroxymonosulfate (PMS) was developed in this study. The ZnFe2O4 catalyst was prepared through co-precipitation, which involves the doping of zinc in iron-based materials. And this process accelerated the redox cycle, which energized the PMS and promoted the generation of free radicals. Electron paramagnetic resonance (EPR) analysis revealed that ZnFe2O4 activates PMS to generate HO•, O2•−, and 1O2, which contribute to ATZ elimination. In this study, a new approach is proposed for the development of efficient heterogeneous catalysts capable of activating PMS and eliminating the ATZ. Moreover, The ATZ degradation pathway was proposed based on the products identified by UPLC-MS. The results highlighted the efficiency of the as-prepared ZnFe2O4 catalyst in ATZ removal and its excellent performance. Given its environmental compatibility and high efficiency, the ZnFe2O4 catalyst has significant potential implications for agricultural wastewater treatment.